(untitled) (American Journal of Pedagogical and Educational Research, 2025)
The training group for long-distance runners has been established to improve the process of athlete preparation. This article explores both the theoretical and practical aspects of long-distance running, as well as focuses on enhancing the physical and psychological condition of athletes. During the training sessions, modern methodologies and techniques are applied by coaches, considering the individual characteristics of each athlete. Special programs aimed at improving the endurance, speed, and strength of the runners are developed. Furthermore, particular attention is given to motivating athletes and strengthening their psychological preparedness. This training group not only helps long-distance runners to prepare physically but also mentally, ultimately contributing to their success in sports.